Consumption smoothing in a balanced budget regim - Lovisa Persson (Uppsala University, Department of Economics, 2013)
I investigate consumption smoothing (sensitivity) under a balanced budget rule in Swedish municipalities. In general, I find Swedish municipalities to be highly consumption sensitive during the time period 2001-2011 when the BBR was in place. A one percentage increase in predicted current revenues leads to a 0.74-0.76 percentage increase in current consumption. I use fiscal indicators - the level of own funds and net operating surplus - as proxies for budget balance boundness. Municipalities that perform well in both these fiscal areas are more smoothing than municipalities that do not perform well in either, implying that budget balance plays a role for consumption smoothing behavior. However, consumption sensitivity has decreased in the aggregate since the implementation of the BBR. A possible story is that municipalities were primarily upward sensitive before the BBR, and primarily downward sensitive after the BBR. This explanation also fits the descriptive picture that the aggregate surplus in the sector has turned to positive from negative since the BBR implementation.
urn:nbn:se:uu:diva-210097
Keywords: H77; H74; D78; D60; 330; Local public finance; Balanced budget rules; Consumption smoothing; Fiscal consolidation; Fiscal institutions